Dinamika Konflik Pemerintah dan Masyarakat dalam Penerapan Kebijakan Pembatasan Usia Media Sosial bagi Anak di Bawah 16 Tahun di Indonesia - Wafa Khosibah; Alfia Nur Aline; Chindika Maulidyah Apriliani; Adha Roh Fifiandari; Nuh Krama Hadianto (Jurnal Ilmu Administrasi Negara, 2026)
This study aims to analyze the dynamics of conflict between the government and society in the implementation of social media age restriction policies for children under 16 years old in Indonesia. The study employs a qualitative approach using a descriptive-analytical method through a literature review of relevant secondary sources. The findings show that the age restriction policy represents a preventive government response to protect children from various digital risks, including exposure to harmful content, cyberbullying, digital exploitation, and misuse of personal data. However, the implementation of this policy faces several challenges arising from differing perceptions between the government and society, technical limitations such as age verification systems, and low levels of digital literacy. These conflicts have led to suboptimal policy implementation in practice, creating a gap between normative policy objectives and empirical realities. The study emphasizes that policy effectiveness is not only determined by regulatory frameworks but also by the readiness of the digital ecosystem, including technological, social, and institutional aspects. Therefore, a collaborative approach is required through strengthening digital literacy, enhancing platform responsibility, and involving families and communities to ensure effective and sustainable policy implementation.